Educação a distância e o CEAR/UEG : análise de uma disciplina a partir de posições e contraposições com a cultura digital - Rodrigues, Thaís Marques Cabral (2024)
The research, entitled “Distance education and CEAR/UEG: analysis of a discipline based on positions and oppositions with Digital Culture,” is linked to the Language and Social Practices research line of the Interdisciplinary Postgraduate Program in Education, Language and Technologies (PPG-IELT) at the State University of Goiás (UEG). Based on the question, what are the possible positions and oppositions with Digital Culture in the Pedagogy course linked to the Open University of Brazil (UAB), offered by the Center for Networked Teaching and Learning (CEAR) of the State University of Goiás (UEG), in the distance modality? The general objective is to analyze a subject in the Pedagogy/UAB course offered by CEAR/UEG in search of positions and oppositions with Digital Culture. The research is qualitative and exploratory in its objectives. It uses bibliographical, documentary, and netnographic research procedures based mainly on the studies of Litto and Formiga (2009), Giolo (2008), Lima (2022), Kenski (2018), and Mill (2012) for a theoretical basis on distance education in higher education; and on the studies by Lemos (2023), Malheiro (2021), Martins (2018), Rodrigues (2020; 2022) and Santaella (2014; 2021) for discussions on Digital Culture. Regarding CEAR, the studies used were Almeida (2022), Oliveira (2019), Rezende, Campos, and Campos (2019), and Stacheira et al. (2015), as well as documents and legislation, such as Decree No. 5.800 of June 8, 2006 (Brasil, 2006), Law no. 9.394, of December 20, 1996 (Brazil, 1996), Resolution no. 1, of March 11, 2016 (Brazil, 2016), Decree no. 9.057, of May 25, 2017 (Brazil, 2017) and other state and institutional documents. The research object comprises the subject of Language, Technologies, and Textual Production of the Pedagogy/UAB course (2017 and 2019) offered by CEAR/UEG. This analysis is believed to be a fruitful field of study for discussions about positions and oppositions to think about new structures in distance education and the areas of Education, Language, and Technologies. Analyzing Language, Technologies, and Textual Production reveals positions and oppositions with Digital Culture. The subject covers discussions on Generation Z, social media, fake news, isolation, and quality of life. Proposed improvements include updating the theoretical framework to encompass academic literacy and Digital Culture. Restructuring involves revisiting classes, reducing grammatical emphasis, and integrating critical analysis of technology's role through inclusive epistemic materials.